A case series of patients with left ventricular assist devices and concomitant mechanical heart valves. Issue 10 (23rd April 2020) - Al Saadi, Tareq; Andrade, Ambar; Chickerillo, Krystina; Joshi, Anjali; Sciamanna, Christopher; Pauwaa, Sunil; Macaluso, Gregory; Dia, Muhyaldeen; Cotts, William; Tatooles, Antone; Pappas, Patroklos
Abstract: Mechanical heart valves left in situ at the time of left ventricular assist device (LVAD) implantation are thought to potentially increase the risk of thromboembolism. Recommendations exist to replace dysfunctional mechanical mitral valves and any mechanical aortic valves at the time of LVAD implantation. Due to potential increases in cardiopulmonary bypass time and associated comorbidities with valve replacement, leaving a functional mechanical valve in place at LVAD implantation has been suggested to be a safe option. We retrospectively reviewed all patients with prior mechanical mitral or aortic valves undergoing LVAD implantation at our center between 2012 and 2017. Echocardiograms were read by a single cardiologist to assess for mechanical valve dysfunction. We identified 15 patients. Five patients had major bleeding requiring transfusion. On follow‐up, 2 patients had hemorrhagic stroke and 2 had transient ischemic attach/ischemic stroke. In addition, 2 patients had LVAD thrombosis and 2 patients had LVAD driveline malfunction. Mild mechanical valve regurgitation was identified on follow‐up echocardiograms of 2 patients. Rate of complications in patients with mechanical valves undergoing LVAD implantation was comparable to that reported for the general LVAD population. Leaving a functional mechanical valve in place at the time of LVAD implantation could be a reasonable alternative to valve replacement. More data are required to further guide patient care in these individuals.